Participatory varietal selection of potato using the mother & baby trial design: A gender-responsive trainer’s guide. - Haan, Stef de; Salas, E.; Fonseca, C.; Gastelo, M.; Amaya, N.; Bastos, C.; Hualla, V.; Bonierbale, Merideth W. (International Potato Center, 2019)
This guide aims to provide step-by-step guidance on facilitating and documenting the PVS dynamics using the MBT design to select, and eventually release, potato varieties preferred by end-users that suit male and female farmers ’different needs, diverse agro-systems, and management practices, as well as traders ’and consumers’ preferences.